2020
DOI: 10.5152/ejbh.2020.5259
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment and Post-Treatment Anxiety, Depression, Sleep and Sexual Function Levels in Patients with Breast Cancer

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The age of women ranged from 25 to 69 years [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]; most were married [1,2,9,18,20,21,24,25,27] and lived in the United States, Germany, or Belgium [9,[15][16][17][18]20,21,23,25]. The types of cancers analyzed in women with sexual dysfunctions were breast, cervical, endometrial, ovarian, vulvar, and gynecological [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, women with cancer were treated with surge...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The age of women ranged from 25 to 69 years [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]; most were married [1,2,9,18,20,21,24,25,27] and lived in the United States, Germany, or Belgium [9,[15][16][17][18]20,21,23,25]. The types of cancers analyzed in women with sexual dysfunctions were breast, cervical, endometrial, ovarian, vulvar, and gynecological [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, women with cancer were treated with surge...…”
Section: Resultsmentioning
confidence: 99%
“…The types of cancers analyzed in women with sexual dysfunctions were breast, cervical, endometrial, ovarian, vulvar, and gynecological [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Additionally, women with cancer were treated with surgery, chemotherapy, radiotherapy, or hormonal therapy [1,2,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. The follow-up time ranged from six months to five years [16][17][18][19][20][21][22][23]25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 However, psychological problems for this duration have been measured less, with the exception of a few longitudinal studies focusing on anxiety and depression. The results of those studies showed that symptoms of anxiety and depression were at high levels before cancer treatment, then either slightly declined 8,9 or increased. 10 Trajectory research found that 9% of patients were consistently anxious and depressed from pre-chemotherapy to 12 months post-chemotherapy.…”
mentioning
confidence: 99%